Stoichiometry [filem jalur] (Fairfield, Conn. : Communication Skills Corp., 1973)
Contents : 1. Atomic weights, molecular weights, and the mole concept -- 2. Formulas and composition calculations -- 3. Formulasfrom analysis of composition of compounds -- 4. Calculations involving equations